Panic disorder during pregnancy and the first three years after delivery: a systematic review - F. Gerrik Verhees; Antonia Bendau; Stefanie Unger; Katharina L. Donix; Eva Asselmann; Julia Martini (BMC Pregnancy and Childbirth)
Abstract Background Panic disorder (PD) is highly prevalent during the peripartum period. The aim of this systematic review was to summarize evidence on risk factors and course patterns of peripartum PD as well as maternal, infant or dyadic outcomes during the first three years after delivery. Methods A literature search was conducted according to PRISMA guidelines. Inclusion criteria were: (1) a diagnosis of PD or panic attacks during pregnancy, (2) risk factors and course as well as maternal, infant or dyadic outcomes measured in pregnancy and/or up to 3 years postpartum (3) peer-reviewed articles in English or German published between 1980 and April 2024. After screening of n = 2,740 records, n = 75 records based on n = 64 projects were eligible for this systematic review. Results Overall, n = 47 studies investigated the course of PD during the peripartum period, n = 23 studies examined the associations of PD and obstetric, neonatal or infant outcomes, and n = 5 studies focused on the associations of PD and characteristics of the mother-infant dyad. We found (1) no common trajectory, but heterogeneous courses of maternal PD in the peripartum period, (2) associations of maternal PD with birth complications and subsequent postpartum depression, and (3) evidence for associations of PD with infant and dyadic outcomes. Limitations Diverse outcome measures in recent original publications did not allow for a meta-analytic approach. Conclusion Heterogenous courses and outcomes of peripartum PD require comprehensive monitoring of affected mothers and their infants. There is a need for further longitudinal investigations into familial transmission of anxiety disorders.